Faktor-Faktor Yang Mempengaruhi Tingkat Masalah Ibu Hamil Mengonsumsi Tablet Fe di Wilayah Kerja Puskesmas Lolak - Alhidayah; Muzayyana; Sitti Nurul Hikma Saleh; Agustin (Gema Wiralodra, 2022)
Iron is a blood-added tablet that can overcome iron nutritional anemia that occurs in pregnant women. Fe tablets are mineral tablets that are needed for the formation of red blood cells (Hemoglobin). This Fe tablet was given as many as 90 grains during her pregnancy. WHO states that there are 40% of maternal deaths in developing countries and the most common is anemia. In Indonesia reached 33.1% anemia occurred. After conducting research in the Lolak Health Center Work Area in 2021, out of 85 respondents, only 30 (35.3%) pregnant women were obedient to consuming Fe tablets. The purpose of this study is to find out what are the factors that influence the level of laziness of pregnant women in consuming Fe tablets in the Lolak Health Center Work Area in 2021. This research method uses an observational design with a Cross Sectional Study research design with a quantitative approach. With a population of pregnant women in the Lolak Health Center working area, which amounted to 51 respondents. The conclusion from this study that there is a relationship between knowledge factors (pvalue = 0.000), side effects (pvalue = 0.003), motivation (pvalue = 0.000) and family support (pvalue = 0.000) with the level of laziness of pregnant women in consuming Fe tablets, it can be concluded that there is a relationship between knowledge and the level of laziness of pregnant women in consuming Fe tablets. Suggestions in this study are for pregnant women to increase their compliance in consuming Fe tablets.